Analisis dan Perancangan Sistem Informasi Penjualan dan Persediaan Barang Pada Gudang Pada CV. KAJEYEFOOD - Annata Rahadiyan; Niken Hendrakusma Wardani; Retno Indah Rokhmawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
CV. KAJEYEFOOD is a company that specialize in the food processing of fruit chips that has been established since 2002 in Malang city. CV. KAJEYEFOOD has a store that sells fruit chips from the company's production. But in practice, the store is still using conventional way in the sales transaction activities. The same thing happens in the warehouse where inventory recording activity was performed manually. To solve this problem, a system that can support business activities in store and warehouse is needed. In this study, the design of information system was done to help solving the problems. The design was done by using Rational Unified Process framework. In the inception phase, requirement analysis produced vision documents, 8 features, 21 functional requirements, 2 non-functional requirements, 9 use cases, and activity diagrams of each use case. In the elaboration phase, the design produced analysis class for each use case, analysis class mapping, unification class analysis, class diagrams, model data, and sequence diagrams. After the analysis and design phase, the evaluation was done by using traceability matrix method and requirement configuration structure (consistency analysis). The results of the evaluations that have been conducted shows that each requirement has a unique code that can be tracked and all the requirements that have been defined are consistent.